2019
DOI: 10.1002/humu.23954
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput custom capture sequencing identifies novel mutations in coloboma‐associated genes: Mutation in DNA‐binding domain of retinoic acid receptor beta affects nuclear localization causing ocular coloboma

Abstract: Uveal coloboma is a potentially blinding congenital ocular malformation caused by the failure of optic fissure closure during the fifth week of human gestation. We performed custom capture high-throughput screening of 38 known colobomaassociated genes in 66 families. Suspected causative novel variants were identified in TFAP2A and CHD7, as well as two previously reported variants of uncertain significance in RARB and BMP7. The variant in RARB, unlike previously reported disease mutations in the ligand-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 117 publications
(191 reference statements)
4
12
0
Order By: Relevance
“…The developmental processes associated with optic fissure closure have been progressively elucidated over the past half century, however, the genetics of uveal coloboma is far from well understood. Indeed, two recent studies were only able to molecularly solve approximately 8-15% of anophthalmia, microphthalmia and coloboma cases, consistent with our own laboratory’s experience 8, 46, 47 . Higher yields for molecular testing have been noted in patients with a clearly defined syndrome 48 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The developmental processes associated with optic fissure closure have been progressively elucidated over the past half century, however, the genetics of uveal coloboma is far from well understood. Indeed, two recent studies were only able to molecularly solve approximately 8-15% of anophthalmia, microphthalmia and coloboma cases, consistent with our own laboratory’s experience 8, 46, 47 . Higher yields for molecular testing have been noted in patients with a clearly defined syndrome 48 .…”
Section: Discussionsupporting
confidence: 81%
“…Mutations in more than 20 different genes have been associated with uveal coloboma. These mutations, however, account for less than 10% of cases in the absence of a clear syndromic diagnosis 7, 8 , implying that additional genes and factors are involved.…”
Section: Introductionmentioning
confidence: 99%
“…This same group of experiments was able to link these events to RAR-regulated genes in both the ventral retina/optic stalk and the periocular mesenchyme and show that genes in both of these regions are independently important in mediating optic fissure closure 86 . Further supporting these findings are several studies that have reported coloboma in both humans and animals associated with mutations in various RA signaling genes 70,86,66,91,90,131,130 .…”
Section: Nutritional Deficiencies/excess a Vitamin A And Its Derivativessupporting
confidence: 61%
“…The genetic causes of uveal coloboma have been well reviewed 17,155,1,159 . Despite significant effort, the yield of current molecular genetic testing of coloboma patients is low, estimated to be about 8% 108 , suggesting environmental causes may contribute to the etiology of this condition 70,108 . The purpose of this article is to review epidemiologic and basic research evidence for possible environmental contributors to coloboma.…”
Section: Introductionmentioning
confidence: 99%
“…Trio exome sequencing was performed as described and variants were filtered for apparent de novo status ( 9 ). Peripheral blood DNA samples from the proband, her two sisters, and her parents and her maternal aunt were also used for a custom panel capture targeting 193 genes followed by Illumina short-read sequencing, as reported ( 10 ). A custom NGS analysis pipeline was used for variant calling and filtering as described ( 11 ).…”
Section: Methodsmentioning
confidence: 99%